Matéria orgânica do solo e emissão de C-CO2 em diferentes manejos e cultivos agrícolas - Thomazini, André (2014)
The soil management practices should be applied in such a way as to ensure sustainable production and quality over the years. Agroecological management and no tillage emphasize the maintenance of soil cover and input of organic matter. Assuming that major